Examining the impact of combining traditional and digital leadership styles on Gen Z engagement in Malaysian SMEs; a focus on employers’ perspectives - Chong, Jasmine Yhun Li (2025)
This study explores how traditional and digital leadership styles affect Generation Z (Gen Z) employees in Malaysian small and medium enterprises (SMEs), with the objective of identifying effective, balanced leadership strategies that enhance leadership effectiveness and improve Gen Z job satisfaction. As Gen Z enters the workforce with distinct expectations—valuing flexibility, purpose, feedback, and digital fluency—many SME leaders face challenges in aligning leadership practices with this generation’s needs. To address this, the study employed an inductive, qualitative research approach using semi-structured interviews with leaders across various industries and age groups. This method provided deep insight into real-world leadership behaviours and perceptions. Findings were structured around three research questions: how leadership styles impact Gen Z retention, the challenges leaders face in applying traditional and digital methods, and the strategies that can bridge these styles to create more effective leadership outcomes. The results showed that neither traditional nor digital leadership in isolation is sufficient. Traditional leadership often lacks adaptability, while digital leadership—if unaccompanied by personal connection—can result in disengagement. Two key themes emerged from the data: synergy, representing the integration of traditional and digital styles, and engagement, referring to the emotional and relational connection Gen Z expects from their leaders. Based on these themes, four strategic practices were identified: balanced communication, guided autonomy, digital integration, and human connection. Together, they form a practical leadership framework tailored to the expectations of Gen Z within Malaysian SMEs. This study not only contributes to leadership literature by addressing a clear generational gap in research but also provides actionable recommendations for SME leaders navigating the complexities of hybrid leadership and workforce diversity. It concludes by recommending further research into sector-specific leadership strategies and the impact of AI-enhanced leadership tools on Gen Z engagement and synergy in the workplace.